2007
DOI: 10.1371/journal.pgen.0030146
|View full text |Cite
|
Sign up to set email alerts
|

“Myc’ed Messages”: Myc Induces Transcription of E2F1 while Inhibiting Its Translation via a microRNA Polycistron

Abstract: The recent revelation that there are small, noncoding RNAs that regulate the expression of many other genes has led to an exciting, emerging body of literature defining the biological role for these molecules within signaling networks. In a flurry of recent papers, a microRNA polycistron induced by the oncogenic transcription factor c-myc has been found to be involved in an unusually structured network of interactions. This network includes the seemingly paradoxical transcriptional induction and translational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
86
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 71 publications
3
86
0
Order By: Relevance
“…Although differential expression of coding mRNA between normal and malignant tissues may differ by orders of magnitude, relatively modest differences of 1-to 2-fold, or less, were commonly seen for individual miRNAs. 5,31,32 This consideration, together with unique technical features in our analysis, may explain the comparatively modest differential T/N expression ratios observed in our study.…”
Section: Discussionmentioning
confidence: 77%
“…Although differential expression of coding mRNA between normal and malignant tissues may differ by orders of magnitude, relatively modest differences of 1-to 2-fold, or less, were commonly seen for individual miRNAs. 5,31,32 This consideration, together with unique technical features in our analysis, may explain the comparatively modest differential T/N expression ratios observed in our study.…”
Section: Discussionmentioning
confidence: 77%
“…5 could explain an experimental observation that seemingly contradicts the prediction of the model at steady state. Several groups (14,25,26) have shown that miR-20a and miR-17-5p (members of the miR-17-92 cluster) are antiapoptotic because the down-regulation of these miRs leads to increased cell death and their overexpression decreases cell death. These observations were explained (25,27) in terms of the down-regulation of E2F1 protein levels by miR-20a and miR-17-5p, and E2F1's induction of apoptosis when overexpressed.…”
Section: Non-steady-state Behavior and Sensitivity Of Protein Levels mentioning
confidence: 99%
“…6). Here, we focus on miR-17-92, which behaves as an oncogene or a tumor suppressor in different situations (2,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although E2F2 and E2F3 are also negatively regulated by miR-17-5p and miR-20a, E2F1 is more strongly affected [88]. The antiapoptotic activity of miR-17-92 miRNAs has been proposed to reflect the distinct physiological roles of different E2Fs in apoptosis [89]. Unlike E2F2 or E2F3, E2F1 has been particularly associated with apoptosis in addition to its function as an activator of cell cycle [90].…”
Section: Mirna With Anti-apoptotic Functionsmentioning
confidence: 99%